Jazz and Machine-Age Imperialism : Music, "Race," and Intellectuals in France, 1918-1945 - Lane, Jeremy F. (Book collections on Project MUSE., 2013)
This book closely examines the reception of jazz among French-speaking intellectuals between 1918 and 1945 and is the first study to consider the relationships, sometimes symbiotic, sometimes antagonistic, between early white French jazz critics and those French-speaking intellectuals of color whose first encounters with the music in those years played a catalytic role in their emerging Black or Creole consciousness. Jazz's first arrival in France in 1918 coincided with a series of profound shocks to received notions of French national identity and cultural and moral superiority. These shocks, characteristic of the era of machine-age imperialism, had been provoked by the first total mechanized war, the accelarated introduction of Taylorist and Fordist production techniques into European factories, and the more frequent encounters with primitive 'Others' in the imperial metropolis engendered by interwar imperialism. Through close readings of the work of early white French jazz critics, alongside the essays and poems of intellectuals of color such as the Nardal sisters, Leon-Gontran Damas, Leopold Sedar Senghor, and Rene Menil, this book highlights the ways in which the French reception of jazz was bound up with a series of urgent contemporary debates about primitivism, imperialism, anti-imperialism, Black and Creole consciousness, and the effects of American machine-age technologies on the minds and bodies of French citizens. -- Page 4 of cover.